2022
DOI: 10.3390/jcm11185482
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Steatohepatitis in Obese Diabetic and Non-Diabetic Patients

Abstract: Background and Aims: The presence of steatohepatitis in obese patients can be multifactorial. The current study tries to determine the differences between diabetic and non-diabetic patients regarding the presence of steatohepatitis. We evaluated sequential liver samples and collected the times of bariatric surgery to assess the presence of NASH in patients with obesity, in the circuit of bariatric surgery. Methods: We performed a retrospective study of 49 patients presenting high-grade obesity in the circuit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…We used both of these indicators to score the degree of hepatic brosis in T2DM patients. We found that 25(OH)D was negatively correlated with FIB4 and FLI, and, moreover, FLI and FIB-4 levels were higher in the low 25 hydroxyvitamin D level group, all of which suggest that 25(OH)D de ciency may promote the progression of hepatic brosis in T2DM patients with NAFLD [25].…”
Section: Discussionmentioning
confidence: 66%
“…We used both of these indicators to score the degree of hepatic brosis in T2DM patients. We found that 25(OH)D was negatively correlated with FIB4 and FLI, and, moreover, FLI and FIB-4 levels were higher in the low 25 hydroxyvitamin D level group, all of which suggest that 25(OH)D de ciency may promote the progression of hepatic brosis in T2DM patients with NAFLD [25].…”
Section: Discussionmentioning
confidence: 66%